Treatment of drug residues (emerging contaminants) in hospital effluent by the combination of biological and physiochemical treatment process: a review. Issue 1 (4th May 2021) - Ahmad, Nadeem; Ahmed, Sirajuddin; Vambol, Viola; Vambol, Sergij
Abstract : Purpose: All those effluent streams having compromised characteristics pose negative effects on the environment either directly or indirectly. Health care facilities and hospitals also generate a large amount of effluent like other industries containing harmful and toxic pharmaceutical residual compounds due to uncontrolled use of drugs, besides others. The occurrence of antibiotic in the environment is of utmost concern due to development of resistant genes. These get mixed up with ground and surface water due to lack of proper treatment of hospital wastewater. The effect of pharmaceutical compounds on human society and ecosystem as a whole is quite obvious. There are no strict laws regarding discharge of hospital effluent in many countries. Contrary to this, the authors do not have appropriate treatment facilities and solution to solve day by day increasing complexity of this problem. Moreover, water discharged from different health facilities having variable concentration often gets mixed with municipal sewage, thus remains partially untreated even after passing from conventional treatment plants. The purpose of this paper is to highlight the occurrences and fate of such harmful compounds, need of proper effluent management system as well as conventionally adopted treatment technologies nowadays all around the globe. This mini-review would introduce the subject, the need of the study, the motivation for the study, aim, objectives of the research and methodology to be adopted for such a study. Design/methodology/approach: Hospital effluents consisting of pathogens, fecal coliforms, Escherichia coli, etc, including phenols, detergents, toxic elements like cyanide and heavy metals such as copper (Cu), iron (Fe), gadolinium (Gd), nickel (Ni), platinum (Pt), among others are commonly detected nowadays. These unwanted compounds along with emerging pollutants are generally not being regulated before getting discharged caused and spread of diseases. Various chemical and biological characteristics of hospital effluents are assessed keeping in the view the threat posed to ecosystem. Several research studies have been done and few are ongoing to explore the different characteristics and compositions of these effluent streams in comparison so as to suggest the suitable conventional treatment techniques and ways to manage the problem. Several antibiotic groups such as ciprofloxacin, ofloxacin, sulfa pyridine, trimethoprim, metronidazole and their metabolites are reported in higher concentration in hospital effluent. The aquatic system also receives a high concentration of pharmaceutical residues more than 14, 000 μ g/L from treatment plants also and other surface water or even drinking water in Indian cities. Many rivers in southern parts of India receives treated water have detected high concentration drugs and its metabolites. As far as global constraints that need to be discussed, there are only selected pharmaceuticals compounds generally analyzed, issue regarding management and detection based on method of sampling, frequency of analysis and observation, spatial as well as temporal concentration of these concerned micropollutants, accuracy in detecting these compounds, reliability of results and predictions, prioritization and the method of treatment in use for such type of wastewater stream. The complexity of management and treatment as well need to be addressed with following issues at priority: composition and characterization of effluent, compatible and efficient treatment technology that needs to be adopted and the environment risk posed by them. The problem of drugs and its residues was not seen to be reported in latter part of 20th century, but it might be reported locally in some part of globe. This paper covers some aspect about the disposal and regulatory standard around the world toward hospital effluent discharge, its managements and treatment technologies that are adopted and best suitable nowadays various industries and monitoring the efficiencies of existing treatment systems. This mini-review would introduce the subject, the need, the motivation and objectives of the study and methodology can be adopted for such a study. Findings: The compiled review gives a complete view about the types of antibiotics used in different health care facilities, their residue formation, occurrences in different ecosystems, types of regulations or laws available in different counties related to disposal, different type of treatment technologies, innovative combined treatment schemes and future action needed to tackle such type of effluent after its generation. The thesis also highlights the use of certain innovative materials use for the treatment like nanoparticles. It also discusses about the residues impact on the human health as well as their bioaccumulative nature. If the authors relate the past to the current scenario of pharmaceutical compounds (PhACs) in the environment, the authors will certainly notice that many diseases are nowadays not curable by simple previously prescribed Ab. Many research projects have been done in European countries that have shown the risk of such residues like Pills, Sibell, Poseidon, No pills, Neptune, Knappe, Endetech, etc. In the previous section, it was mentioned that there are no stringent laws for hospital wastewater and in many countries, they are mixed with domestic wastewater. Many difficulties are there with this research due to complex analysis, detection of targeted Ab, affecting waterbodies rate of flow, nature of treatment varies with season to season. The way nature is being degraded and harmful effect are being imposed, it is important to take immediate and decisive steps in this area. Wastewater treatment plants (WWTPs) serves as a nursery for antibiotic-resistant systems, hence monitoring with great attention is also needed. Many trials with different treatment process, in combination, were considered. Many countries are paying great attention to this topic by considering the severity of the risk involved in it. Research limitations/implications: Previous studies by several scientists show that the pharmaceutical residues in the discharged effluent displayed direct toxic effects, and sometimes, detrimental effects in the mixture were also observed. The discharge of untreated effluent from hospitals and pharmaceuticals and personal care products in the natural ecosystem poses a significant threat to human beings. The pharmaceuticals, like antibiotics, in the aquatic environment, accelerate the development of the antibiotic-resistant genes in bacteria, which causes fatal health risks to animals and human beings. Others, like analgesics, are known to affect development in fishes. They also degrade the water quality and may lead to DNA damage, toxicity in lower organisms like daphnia and have the potential to bioaccumulate. A few commonly used nanoadsorbents for water and wastewater treatment along with their specific properties can also be used. The main advantages of them are high adsorption capacity and superior efficiency, their high reusability, synthesis at room temperatures, super magnetism, quantum confinement effect as well as eco-toxicity. This review will focus on the applicability of different nanoscale materials and their uses in treating wastewater polluted by organic and inorganic compounds, heavy metals, bacteria and viruses. Moreover, the use of various nanoadsorbents and nano-based filtration membranes is also examined. Practical implications: A number of different pharmaceutical residues derived from various activities like production facilities, domestic use and hospitals have been reported earlier to be present in groundwater, effluents and rivers, they include antibiotics, psycho-actives, analgesics, illicit drugs, antihistamine, etc. In past few years environmental scientists are more concerned toward the effluents generated from medical care facilities, community health centers and hospitals. Various chemical and biological characteristics of hospital effluents have been assessed keeping in the view the common threats pose by them to the entire ecosystem. In this study, seven multispecialty hospitals with nonidentical pretreatment were selected for three aspects i.e. conventional wastewater characteristics, high priority pharmaceuticals and microbial analyses. The present work is to evaluate efficacy of advanced wastewater treatment methods with regard to removal of these three aspects from hospital effluents before discharge into a sewage treatment plant (STP). Based on test results, two out of seven treatment technologies, i.e. MBR and CW effectively reducing conventional parameters and pharmaceuticals from secondary and tertiary treatments except regeneration of microbes were observed in tertiary level by these two treatments. Social implications: This review has aimed to identify the emerging contaminants, including pharmaceutical residues, highly consumed chemicals that are present in the hospital effluent, along with their physicochemical and biological characteristics. In this, the main objective was to review the occurrences and fate of common drugs and antibiotics present in effluents from hospital wastewaters. As far as global constraints that need to be discussed, there are only selected pharmaceuticals compounds generally analyzed, issue regarding management and detection based on method of sampling, frequency of analysis and observation, spatial as well as temporal concentration of these concerned micropollutants, accuracy in detecting these compounds, reliability of results and predictions, prioritization and the method of treatment in use for such type of wastewater stream are among the major issues (Akter et al., 2012; Ashfaq et al., 2016; García-Mateos et al., 2015; Liu et al., 2014; Mubedi et al., 2013; Prabhasankar et al., 2016; Sun et al., 2016; Suriyanon et al., 2015; Wang et al., 2016; Wen et al., 2004). This paper covers some aspect about the disposal and regulatory standard around the world toward hospital effluent discharge, its managements and treatment technologies that are adopted and best suitable nowadays. Originality/value: This study many multispecialty hospitals with nonidentical pretreatment were selected for three aspects i.e. conventional wastewater characteristics high priority pharmaceuticals and microbial analyses. The present work is to evaluate efficacy of advanced wastewater treatment methods with regard to removal of these three aspects from hospital effluents before discharge into an STP. Based on test results, two out of different treatment effectively reducing conventional parameters and pharmaceuticals from secondary and tertiary treatments except regeneration of microbes were observed in the tertiary level by these two treatments were studies followed by ozonation and ultraviolet-ray treatment.